Religious Education in Agricultural Environments: Integrating Islamic Teachings and Agricultural Practices for Holistic Student Development - Masturin (Religious education, 2025)
This study explores a unique approach combining religious education with agriculture at Al Kautsar Integrated Islamic Elementary School in Kudus, Indonesia. Notable for its farmlands, the school integrates agricultural practices with religious studies. Employing a descriptive-thematic method, the research discussed in this article involved collecting data through semi-structured interviews with key stakeholders and analyzing school documents to understand the integration process. Thematic analysis revealed that integrating the Islamic concept of tadabbur (contemplation of nature) in second-grade (typically around seven or eight years old) religious studies, alongside practical farming, enhances student engagement and reduces home-learning monotony. This model fosters nature appreciation, agricultural skills, and emotional well-being. Practical implications suggest that educators can adopt similar integrative approaches to enhance student engagement and well-being. Policymakers should consider supporting schools with resources for environmental education to foster holistic development. However, the applicability of this model is limited by the specific cultural and religious context, the availability of resources such as farmland and educational infrastructure, and the level of commitment from stakeholders, necessitating adaptation and further research to address these challenges in diverse environments. This study explores the benefits of integrating religious education with an agricultural environment in an Islamic elementary school. Al Kautsar Integrated Islamic Elementary School in Kudus, Indonesia, serves as an example, as it combines Islamic teachings with hands-on agricultural experiences for its students. The school uses its extensive agricultural land, including rice, corn, and vegetable fields, fish ponds, and goat sheds, to teach students about nature and farming. These activities not only make learning more engaging but also help reduce anxiety from extended periods of time spent studying at home. The program aims to instill a love for nature, develop practical skills in agriculture, and promote mental and spiritual well-being. This innovative approach could serve as a model for other schools seeking to create a unique and beneficial learning environment. We encourage educators, policymakers, and communities to consider adopting similar integrations in their educational strategies to enhance student learning and well-being.